La “nuova” Costituzione russa e il suo codice di civiltà (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The 2020 amendments of the Russian Constitution opened a new legal and political course, without betraying the spirit of the 1993 Constitutional Charter. The original structure was left untouched, along with its strong presidential connotation. Given the several elements of continuity in the reformed text, it would be inappropriate to speak of a “paradigm shift”. Its “innovative” element, though, consists of a unique combination of principles contained in the Constitution, an architecture – developed during Putin’s twenty years of government – whose pillars are the primacy of sovereign democracy and the affirmation of parameters of civilization, which form the immanent substance of the development strategy of contemporary Russia.
Keywords: Russian Constitution; Sovereign democracy; State-civilization; Orthodox Church; Authoritarianism; Power Vertical